2018
DOI: 10.1002/eet.1801
|View full text |Cite
|
Sign up to set email alerts
|

Framing the debate: How interest groups influence draft rules at the United States Environmental Protection Agency

Abstract: Scholars have identified that interest groups can be most influential on regulatory outcomes during the preproposal stage of the rulemaking process, yet this stage is notoriously understudied.Recently, Rinfret concluded that interest groups use three frames (expertise, fiscal feasibility and instructive) to influence agency personnel at the United States Fish and Wildlife Service.Of the three, the expertise frame was considered most effective. This work confirms these findings across three more significant rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Scholars are somewhat divided on which stakeholders are most influential at this stage in the process. Wagner, Barnes, and Peters () suggest that business interests are most influential, while others suggests this influence is more balanced (Cook, , ; Rinfret, ). For example, Rinfret () concludes that the most influential stakeholders at this stage are not determined by group affiliation, but rather the arguments they make.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars are somewhat divided on which stakeholders are most influential at this stage in the process. Wagner, Barnes, and Peters () suggest that business interests are most influential, while others suggests this influence is more balanced (Cook, , ; Rinfret, ). For example, Rinfret () concludes that the most influential stakeholders at this stage are not determined by group affiliation, but rather the arguments they make.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Kerwin and Furlong’s seminal survey () on interest group participation in federal rulemaking covers a variety of interest groups including business, trade association, and public interests, while excluding state government participants. In fact, most research on interest groups compares the influence of business and public interest organizations, without mention of the presence or influence of state agencies (Cook, , ; Golden, ; Kamieniecki, ; Rinfret, ; Wagner et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, interest groups attempt to influence outcomes at the pre-proposal stage via their informal interactions with agency personnel (Hoefer & Ferguson, 2007;Naughton et al, 2009;West, 2009;Rinfret, 2011b;Yackee, 2012). In the context of the EPA, scholars (Kamieniecki, 2006;Rinfret, 2011b;Cook, 2018a) have concluded that interest groups exert influence via their strategic framing efforts. Not all interest groups are influential at this stage of the process, and Rinfret (2011b) posited that those interest groups that frame their arguments in scientific and technical terms are more likely to impact regulatory outcomes.…”
Section: Interest Group Influence On Regulatory Outcomesmentioning
confidence: 99%
“…Whereas the effect of conflict framing has been studied by political scientists in terms of effects on perceptions of political parties and partisan policy issues, there has been little attention in the environment domain despite broad examination of the effect of frames more generally on attitudes toward environmental issues (Davies et al ; Cook ). In the land use change context, some research with U.S. university student samples has provided insight into the effect of conflict framing on attitudes toward land use change (Schroeder ; Vining and Schroeder ).…”
Section: Introductionmentioning
confidence: 99%